Gender differences in attitudes toward assisted reproduction in the Spanish population: The weight of religiosity and conservatism - Aurrekoetxea-Casaus, Maite; Ronda, Lorena; Govillard, Leila (Frontiers in Political Science, 2022)
The continuous increase in assisted reproductive treatments (ARTs) has generated different ethical dilemmas in the scientific and academic debate. However, there are a few occasions when Spanish citizenship pronounces itself on this issue. It seems that the population has assumed ARTs without questioning despite being a subject crossed by gender mandates that make women the centre of ART application. This study delves into the attitudes of the Spanish population towards assisted reproduction and the persistence of gender mandates in the choice of ARTs, beyond the apparent (almost fixed image of the) total acceptance of ARTs. A questionnaire was applied to a sample of 1030 randomly selected people. Variables included attitudes towards the different possibilities of assisted reproduction, different approaches depending on whether infertility or sterility fell on the woman or the man and other scenarios related to genetic dilemmas. The results of a mean difference test confirmed the high acceptance of ARTs by the Spanish population and revealed significant gender differences. Women accepted ARTs for infertility and genetic disorders, while men accepted ARTs for choosing a baby’s sex. However, gender was not the only relevant variable in the conducted linear regression model; religiosity and political conservatism were also explanatory variables for the acceptance of ARTs. This study is a clear contribution to the debate on the impact of “medicalisation” on women regarding assisted reproduction, showing the persistence of motherhood as a gender mandate.